Boards of directors and capital structure: Alternative forms of corporate restructuring - Maug, Ernst (Journal of Corporate Finance, 1997)
This paper discusses a model that combines internal and external control mechanisms in a firm in which assets can have alternative uses that are in some states more profitable than the current one. However, restructuring a firm in order to realize the gains from alternative uses affects managers adversely since they invest in firm-specific human capital. Managers can be motivated to restructure the firm through their compensation scheme. Alternatively, investors can acquire costly information on the firm and interfere with managers' decisions. The main focus is on independent directors, who review and monitor contracts and managers' compensation. If information is not too costly, directors are the optimal institution to check managerial discretion and the degree of managerial entrenchment depends on the compensation of independent directors. However, if directors fail to exercise control over management properly, takeovers or creditor control become second-best solutions. If information is costly to transfer, unchecked managerial control may be optimal.